Microbial metabolites and heart failure: Friends or enemies? - Xiaofeng Lu; Jingjing Liu; Jingjing Liu; Bing Zhou; Shuwei Wang; Zhifang Liu; Fuyang Mei; Junxiang Luo; Yong Cui (Frontiers in Microbiology, 2022)
Heart failure (HF), a global health issue characterized by structural or functional cardiac dysfunction, which was found to be associated with the gut microbiome recently. Although multiple studies suggested that the gut microbiome may have an impact on the development of cardiovascular diseases, the underlying mechanism of the gut microbiome in HF remains unclear. The study of metabolites from gut microbiota influenced by dietary nutrition uptake suggested that gut microbiota may affect the process of HF. However, on the basis of the microbiota’s complicated roles and their interactions with metabolites, studies of microbial metabolites in HF had rarely been described so far. In this review, we focused on dietary nutrition-related factors that were involved in the development and progression of HF, such as trimethylamine N-oxide (TMAO), short-chain fatty acids (SCFAs), and bile acids (BAs), to summarize their advances and several potential targets in HF. From a therapeutic standpoint, we discussed microbial metabolites as a potential strategy and their applications in HF as well.